Synergistically competitive coordination for tailoring sodium cointercalation potential of graphite - Jiali Wang; Shiqi Li; Ming Chen; Chongwei Gao; Wei Li; Guang Feng; Feiyu Kang; Dengyun Zhai (Nature Communications)
Abstract Sodium co-intercalation in graphite negative electrodes delivers high-rate kinetics, and yet its implementation is plagued by notorious reaction potential. While prior efforts reduce the co-intercalation potential, the design remains limited by the intrinsic properties of electrolyte. Herein, a flexible design strategy based on synergistically competitive coordination is developed to tailor co-intercalation potential in dilute ether systems. The electrolyte design simultaneously diminishes the size and number of intercalated solvents into graphite galleries that enable milder intercalation mechanism, distinctive intercalant distribution, and less stable Na-dimethyl ether coordination. Without sacrificing fast kinetics, the co-intercalation potential of graphite negative electrode is tailored to 0.4 V after incorporating dimethoxymethane, even reaching a level of 0.32 V at evaluated temperature (60 °C). The resultant promotion of average operating voltage and inheritable rate capability are verified in sodium-ion full batteries. This design concept is applicable for screening other sets of small-weak co-solvents and providing guidance for more potential regulation electrolytes.